Extending the net: from securitisation to civicisation of migration control - Klaus, Witold (Crime prevention and community safety, 2021)
The article aims to contribute to the very actual theoretical debate concerning intersection of migration control and crime prevention. Its objective is to review and critically discuss the process of extending control over immigrants. It is based on the analysis of control practices revealed in the countries of the Global North, which are the most common destinations for immigrants, be they forced or voluntary. We apply the three-stage notion of the development of migration control, of which two, i.e. securitisation and privatisation, have been quite extensively commented on in the literature so far. The third level, though, based on civic involvement in migration control practices, named here civicisation of migration control, deserves special attention as possibly prospective tool applied by the states in migration governance. We claim that increasing the net of social agents encouraged or obliged to control and report to authorities “suspicious” migrants or their “suspicious” behaviours raises doubts whether the involvement of citizens of certain kinds of public and private bodies can be assessed positively. To support this argument, we indicate the consequences of unreflexive associations of migration-related phenomena with threats to security and crimes.